Wing-strain-based flight control of flapping-wing drones through reinforcement learning - Kim, Taewi; Hong, Insic; Im, Sunghoon; Rho, Seungeun; Kim, Minho; Roh, Yeonwook; Kim, Changhwan; Park, Jieun; Lim, Daseul; Lee, Doohoe; Lee, Seunggon; Lee, Jingoo; et al. (Nature Machine Intelligence, 2024)
Although drone technology has advanced rapidly, replicating the dynamic control and wind-sensing abilities of biological flight is still beyond reach. Biological studies reveal that insect wings are equipped with mechanoreceptors known as campaniform sensilla, which detect complex aerodynamic loads critical for flight agility. By leveraging robotic experiments designed to mimic these biological systems, we confirm that wing strain provides crucial information about the drone’s attitude angle, as well as the direction and velocity of the wind. We introduce a wing-strain-based flight controller that employs the aerodynamic forces exerted on a flapping drone’s wings to deduce vital flight data such as attitude and airflow without accelerometers and gyroscopic sensors. The present work spans five key experiments: initial validation of the wing strain sensor system for state information provision, control in a single degree of freedom movement environment with changing winds, control in a two degrees of freedom movement environment for gravitational attitude adjustment, a test for position control in windy conditions and a demonstration of precise flight path manipulation in a windless condition using only wing strain sensors. We have successfully demonstrated control of a flapping drone in various environments using only wing strain sensors, with the aid of a reinforcement-learning-driven flight controller. The demonstrated adaptability to environmental shifts will be beneficial across varied applications, from gust resistance to wind-assisted flight for autonomous flying robots.
Keywords: Dynamic controls; Dynamic winds; Flapping-wing; Flight control; Flight controllers; Reinforcement learnings; Sensing abilities; Strain based; Strain sensors; Wind sensing